The Role of Youth in Tourism Awareness Movement in West Detusoko Tourism Village, Ende Regency - Adja Mosa, Yohanes A (SABA: Journal of Tourism Research, 2024)
This study investigates the pivotal role of local youth in promoting tourism awareness. The research is conducted inDetusoko Barat Village, located within the Detusoko District of Ende Regency, East Nusa Tenggara. Employing a qualitative research design, the study utilises purposive sampling to identify participants. Data collection methods included observation and in-depth interviews to seven informants to gain comprehensive insights into their experiences and perspectives. The findings indicate that while the youth in Detusoko Barat are positioned as vital agents of change and development within the context of tourism, their roles in advancing the tourism awareness movement are not being fully realised. The research highlights gaps in engagement, suggesting that further efforts are needed to empower youth and optimise their contributions to tourism development. Ultimately, this study underscores the importance of actively involving local youth in tourism initiatives. It advocates for strategies to enhance their roles, promoting a more robust and conscious tourism culture in Detusoko Barat Village.